Original paperTreatment of left main coronary artery stenosis with the STENTYS self-expandable drug-eluting stent – a pilot registry - Smolka, Grzegorz; Wańha, Wojciech; Roleder, Tomasz; Pluta, Aleksandra; Ochała, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Percutaneous coronary intervention (PCI) of the left main coronary artery (LMCA) for revascularization after stenosis is still considered controversial therapy. Previous studies were performed with balloon-expandable drug-eluting stents (DES). Balloon-expandable stents presented a challenge because they were not able to adapt effectively to variation in the vessel lumen. There are limited data on LMCA therapy with self-expandable DES for treatment of medial and distal lesions. The advantages of a self-apposing stent are adaptation to vessel size, vessel tapering, stent sizing, and good apposition. This was a pilot study to determine safety and device success rate in patients with middle and distal LMCA stenosis treated with the STENTYS self-expanding coronary DES stent. The primary endpoints were device success, acute procedural success and in-hospital and 30-day MACE. Twenty-four patients were included. Median logistic EuroSCORE was 1.6% (1.1–2.6%). Median Syntax score was 20.0 (20.0–27.2) points. Significant stenosis according to the anatomical region was in the middle of the LMCA in 5 cases (21%) and the distal part in 19 (79%). Stent sizes used were: 3.0 × 3.5 mm in 9 (37.5%); 3.5 × 4.0 mm in 3 (12.5%); 3.5 × 4.5 mm in 12 (50%). Device success and acute procedural success were achieved in 23 patients (95.8%), with no edge dissection in any patient. In 1 patient the proximal end of the stent protruded into the aorta. In all patients during their hospitalization and 30-day follow-up there were no adverse events. The data compiled from this small, single-center pilot study suggest that the STENTYS self-expanding coronary stent may be a reasonable approach to treat lesions within the LMCA. These results warrant a larger future clinical trial.